Indirect effects of soil amendments on plant traits and the microbiome in post-wildfire forest recovery - David M. Barnard; Adam L. Mahood; Jacob A. Macdonald; Kaela K. Amundson; Timothy S. Fegel; Sean M. Gleason; Madeline Guimond; Sophie Kaiser; Kya Sparks; Michael J. Wilkins; Charles C. Rhoades (Forest Ecology and Management, 2025)

Surface boundary layer stability and meteorological drivers of temporal microclimate variability in a semiarid grassland - David M Barnard; Jacob Macdonald; Robert H. Erskine; Timothy R. Green; Adam Mahood; Sean M. Gleason (Agricultural and Forest Meteorology, 2025)

Comparative venation costs of monocotyledon and dicotyledon species in the eastern Colorado steppe - Sarah Tepler Drobnitch; J. A. Kray; Sean M. Gleason; Troy W. Ocheltree (Planta, 2024)

Searching for mechanisms driving root pressure in Zea mays—a transcriptomic approach - Sarah Tepler Drobnitch; Joshua Wenz; Sean M. Gleason; Louise H. Comas (Journal of Plant Physiology, 2024)

Coordination of photosynthetic traits across soil and climate gradients - Andrea C. Westerband; Ian J. Wright; Vincent Maire; Jennifer Paillassa; Iain Colin Prentice; Owen K. Atkin; Keith J. Bloomfield; Lucas A. Cernusak; Ning Dong; Sean M. Gleason; Caio Guilherme Pereira; Hans Lambers; et al. (Global Change Biology, 2023)
“Least‐cost theory” posits that C 3 plants should balance rates of photosynthetic water loss and carboxylation in relation to the relative acquisition and maintenance costs of resources required for these activities. Here we investigated the dependency of photosynthetic traits on climate and soil properties using a new Australia‐wide trait dataset spanning 528 species from 67 sites. We tested the hypotheses that plants on relatively cold or dry sites, or on relatively more fertile sites, would typically operate at greater CO 2 drawdown (lower ratio of leaf internal to ambient CO 2 , C i : C a ) during light‐saturated photosynthesis, and at higher leaf N per area (N area ) and higher carboxylation capacity ( V cmax 25 ) for a given rate of stomatal conductance to water vapour, g sw . These results would be indicative of plants having relatively higher water costs than nutrient costs. In general, our hypotheses were supported. Soil total phosphorus (P) concentration and (more weakly) soil pH exerted positive effects on the N area – g sw and V cmax 25 – g sw slopes, and negative effects on C i : C a . The P effect strengthened when the effect of climate was removed via partial regression. We observed similar trends with increasing soil cation exchange capacity and clay content, which affect soil nutrient availability, and found that soil properties explained similar amounts of variation in the focal traits as climate did. Although climate typically explained more trait variation than soil did, together they explained up to 52% of variation in the slope relationships and soil properties explained up to 30% of the variation in individual traits. Soils influenced photosynthetic traits as well as their coordination. In particular, the influence of soil P likely reflects the Australia's geologically ancient low‐relief landscapes with highly leached soils. Least‐cost theory provides a valuable framework for understanding trade‐offs between resource costs and use in plants, including limiting soil nutrients.

Leaf manganese concentrations as a tool to assess belowground plant functioning in phosphorus-impoverished environments - Hans Lambers; Ian J. Wright; Caio Guilherme Pereira; Peter J. Bellingham; Lisa Patrick Bentley; Alex Boonman; Lucas A. Cernusak; William Foulds; Sean M. Gleason; Emma F. Gray; Patrick E. Hayes; Robert M. Kooyman; et al. (Plant and Soil, 2021)

Growing‐season temperature and precipitation are independent drivers of global variation in xylem hydraulic conductivity - Pengcheng He; Sean M. Gleason; Ian J. Wright; Ensheng Weng; Hui Liu; Shidan Zhu; Mingzhen Lu; Qi Luo; Ronghua Li; Guilin Wu; Enrong Yan; Yanjun Song; et al. (Global Change Biology, 2020)
Stem xylem‐specific hydraulic conductivity ( K S ) represents the potential for plant water transport normalized by xylem cross section, length, and driving force. Variation in K S has implications for plant transpiration and photosynthesis, growth and survival, and also the geographic distribution of species. Clarifying the global‐scale patterns of K S and its major drivers is needed to achieve a better understanding of how plants adapt to different environmental conditions, particularly under climate change scenarios. Here, we compiled a xylem hydraulics dataset with 1,186 species‐at‐site combinations (975 woody species representing 146 families, from 199 sites worldwide), and investigated how K S varied with climatic variables, plant functional types, and biomes. Growing‐season temperature and growing‐season precipitation drove global variation in K S independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes. This highlights an important role for K S in predicting shifts in community composition in the face of climate change.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Balancing the costs of carbon gain and water transport: testing a new theoretical framework for plant functional ecology - I. Colin Prentice; Ning Dong; Sean M. Gleason; Vincent Maire; Ian J. Wright (Ecology Letters, 2014)
A novel framework is presented for the analysis of ecophysiological field measurements and modelling. The hypothesis ‘ leaves minimise the summed unit costs of transpiration and carboxylation ’ predicts leaf‐internal/ambient CO 2 ratios ( c i /c a ) and slopes of maximum carboxylation rate ( V cmax ) or leaf nitrogen ( N area ) vs . stomatal conductance. Analysis of data on woody species from contrasting climates (cold‐hot, dry‐wet) yielded steeper slopes and lower mean c i /c a ratios at the dry or cold sites than at the wet or hot sites. High atmospheric vapour pressure deficit implies low c i /c a in dry climates. High water viscosity (more costly transport) and low photorespiration (less costly photosynthesis) imply low c i /c a in cold climates. Observed site‐mean c i /c a shifts are predicted quantitatively for temperature contrasts (by photorespiration plus viscosity effects) and approximately for aridity contrasts. The theory explains the dependency of c i /c a ratios on temperature and vapour pressure deficit, and observed relationships of leaf δ 13 C and N area to aridity.

Setbacks to shoot growth are common in woody plants, so how are shoots of some species safer than others? - Don W. Butler; Sean M. Gleason; Mark Westoby (Ecology, 2012)
Tissue turnover is a critical facet of plant life history variation. This study quantifies losses from setbacks to growth of terminal woody shoots 1.2 m long, across 83 species and seven sites in eastern Australia. Setbacks, where the leading meristem had been removed or died and a new leader had emerged, were common (median three per shoot). Shoots had lost an average of 0.25 m of lead‐stem length for 1.2 m net shoot‐length gain. Insects like girdlers and borers were prominent causes of large setbacks. The sites spanned tropical to temperate and humid to semiarid climates, but variation in stem loss was much greater across species than across sites. We measured 17 plant functional traits related to growth form, mechanics, hydraulics, and economics. Only four traits were correlated with variation across species in stem losses: stem diameter, stem nitrogen content, bark thickness, and maximum photosynthetic rate. The correlations were weak. Stem specific gravity (wood density) showed no correlation with risk. Our results suggest a pattern similar to the growth–risk trade‐off known for herbaceous plants, where traits associated with fast growth increase tissue turnover and herbivory, but the weak correlations leave ample scope for other influences that remain to be identified.

Species–soil associations, disturbance, and nutrient cycling in an Australian tropical rainforest - Sean Michael Gleason; Jennifer Read; Adrian Ares; Daniel J. Metcalfe (Oecologia, 2010)

Cyclone Effects on the Structure and Production of a Tropical Upland Rainforest: Implications for Life-History Tradeoffs - Sean M. Gleason; Laura J. Williams; Jennifer Read; Daniel J. Metcalfe; Patrick J. Baker (Ecosystems, 2008)

Assessing and Mitigating the Effects of Windblown Soil on Rare and Common Vegetation - Sean M. Gleason; Dave T. Faucette; Mai M. Toyofuku; Carlos A. Torres; Calvin F. Bagley (Environmental Management, 2007)